2008
DOI: 10.1253/circj.72.378
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Late Gadolinium Enhancement and Diastolic Function in Hypertrophic Cardiomyopathy Assessed by Magnetic Resonance Imaging

Abstract: Background Diastolic dysfunction is common in patients with overt hypertrophic cardiomyopathy (HCM). Steady-state cine magnetic resonance imaging (MRI) enables measurement of the diastolic function of the left ventricle (LV), and late gadolinium enhanced MRI can delineate the presence and extent of fibrosis in HCM. The purpose of this study was to determine the relationship between the extent of myocardial fibrosis demonstrated by late gadolinium-enhanced MRI and diastolic dysfunction. Methods and Results Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 33 publications
5
26
0
Order By: Relevance
“…LVMI and the presence of LGE were, however, independent determinants of abnormal diastolic parameters in our study. These findings are not surprising because LVH and myocardial fibrosis 25,26 are well-established causes of diastolic dysfunction. In contrast, Rijzewijk et al 27 and Ng et al 7 demonstrated that steatosis in their diabetic cohort is independently associated with LV diastolic dysfunction using MRI-derived E/A ratio and deceleration time, and longitudinal strain rate measured by echocardiographic speckle tracking, respectively.…”
Section: Myocardial Steatosis In Asmentioning
confidence: 90%
“…LVMI and the presence of LGE were, however, independent determinants of abnormal diastolic parameters in our study. These findings are not surprising because LVH and myocardial fibrosis 25,26 are well-established causes of diastolic dysfunction. In contrast, Rijzewijk et al 27 and Ng et al 7 demonstrated that steatosis in their diabetic cohort is independently associated with LV diastolic dysfunction using MRI-derived E/A ratio and deceleration time, and longitudinal strain rate measured by echocardiographic speckle tracking, respectively.…”
Section: Myocardial Steatosis In Asmentioning
confidence: 90%
“…[1][2][3][4][5] Morphologic expression regarding the site and extent of LVH can often be heterogeneous. There has been some controversy, and confusion, regarding the apical phenotype of HCM, in which hypertrophy of the myocardium predominantly involves the apex of the LV, because of the different diagnostic modalities used by investigators and the various morphologic presentations of apical hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…34 A magnetic resonance imaging study demonstrated that the extent of myocardial fibrosis has a significant correlation with both the LVEF and peak filling rate. 35 The ε is nominally a systolic parameter, whereas elastic recoil, which is determined by the LV end-systolic volume, is an important determinant of the relaxation rate. 36 LV systolic performance is thus dependent on LV diastolic performance.…”
Section: Relation Between Endomyocardial Radial Strain and LV Relaxationmentioning
confidence: 99%